MiR-3614-5p Is a Potential Novel Biomarker for Colorectal Cancer - Han, Lin; Sun, Yanjun; Lu, Cansheng; Ma, Chungeng; Shi, Jian; Sun, Dengqun (Frontiers in Genetics, 2021)
MiR-3614-5p has been found in a variety of cancers including colorectal cancer. However, it's still unclear how miR-3614-5p is related to colorectal cancer. Based on the Cancer Genome Atlas (TCGA) database, the relationship between miR-3614-5p and colorectal cancer can be proved. Wilcoxon rank-sum test is used to compare the miR-3614-5p expression in tissues with colorectal cancer and under normal conditions, respectively. Then, the logistic regression method is employed to analyze the relationship between miR-3614-5p and clinicopathological characteristics. Also, the correlation between miR-3614-5p and survival rate is evaluated by Kaplan-Meier and Cox regression analysis. Besides, gene set enrichment analysis (GSEA) is used to note the biological functions of miR-3614-5p. The decrease of miR-3614-5p expression of colorectal cancer is greatly correlated with N stage(OR) = 0.7 for N1&N2 vs. N0), M stage (OR = 0.5 for M1 vs. M0), pathologic stage (OR = 0.7 for Stage III&Stage IV vs. Stage I&Stage II), neoplasm type (OR = 0.5 for rectum adenocarcinoma vs. colon adenocarcinoma), and lymphatic invasion (OR = 0.6 for YES vs. NO) (all p-values < 0.05). Kaplan-Meier survival analysis shows that colorectal cancer with low miR-3614-5p has a poorer prognosis than that of high miR-3614-5p (p = 0.005). According to univariate analysis, low miR-3614-5p is associated with poor overall survival (OS) (hazard ratio [HR] = 0.599; 95% confidence interval [CI]: 0.418-0.857; p = 0.005). In multivariate analysis, miR-3614-5p is closely related to OS (HR = 0.630; 95% CI: 0.405-0.978, p = 0.021). GSEA shows that the high expression phenotype of miR-3614-5p differentially enriches the P53 pathway. Meanwhile, the high expression phenotype of miR-3614-5p enhances NK T cell activation, negative T cell selection, response to interleukin 2 and response to tumor cells. MiR-3614-5p is a possible prognostic marker of low survival rate for patients with colorectal cancer. Moreover, the P53 pathway and P38MAPK pathway may be the key pathways regulated by miR-3614-5p in colorectal cancer.